THE EFFORT TO INCREASE MATHEMATICS LEARNING COOPERATION BY USING COOPERATIVE MODEL OF NUMBERED HEADS TOGETHER TYPE OF STUDENTS CLASS VIII - Eka Namita Kristumurti; Romelan Hamzah (Universitas Ahmad Dahlan, 2020)
This research is motivated by the lack of student learning cooperation in learning mathematics. This study aims to improve student learning cooperation using the Numbered Heads Together (NHT) type of cooperative learning model for class VIII students of State Junior High Schol (SMP Negeri) 1 Pleret, Bantul Regency in the academic year 2019/2020. Research is a research action class that comprises over two cycles. Setting the research sets class VIII E SMP Negeri 1 Pleret half even regency of Bantul year lesson 2019/2020, with 32 students. Data collection methods used were observation and interviews. The instruments used were observation sheets, interview guidelines, and field notes. The test instrument that is used is the test of the validity of the content. Analysis of the data used is descriptive qualitative. The study results showed that the cooperative learning type NHT improved cooperation learning math student class VIII semester of even SMP Negeri 1 Pleret District Bantul years mop teachings of 2019/2020. This is evident from observations of students' mathematics learning collaboration, which has increased every cycle. In cycle I percentage of cooperative learning of mathematics students is 55,49 % with the criteria sufficiently. In cycle II the percentage of students mathematics learning cooperation was 78,89 % with good criteria. Interviews with students showed that students are interested and feel happy to learn math using a model of learning cooperative type NHT.